Speed skating temporal characteristics from the 1998 Winter Olympics and World Championships - Dutto , D.; Smith, G. A. (1999)
From the percent reduction in velocity values, in general, faster skaters maintained a more constant velocity over the course of a 5000 m race when compared to the field. Pacing strategy was clearest for the women medalists who maintained very consistent skating speed throughout the races. Medalists in the men's races were not exceptional in their pacing abilities and exhibited some substantial drop-off in skating speed.